New g-C3N4 based photocatalytic cement with enhanced visible-light photocatalytic activity by constructing muscovite sheet/SnO2 structures. (10th August 2018) - Peng, Fengping; Ni, Yaru; Zhou, Qiang; Kou, Jiahui; Lu, Chunhua; Xu, Zhongzi
Graphical abstract: Highlights: We explored stable and active photocatalytic cement based on the g-C3 N4 for the first time. The construction of muscovite sheets can improve the stability of photocatalytic cement. The photocatalytic cement can degrade volatile isopropyl alcohol or Rhodamine B stains on its surface tempestuously. Abstract: An imperative new trend of the green construction industry is to integrate photocatalytic technology with building materials. Here, novel g-C3 N4 based photocatalytic cement has been designed for the first time, which mainly integrates three functional modules, i.e. g-C3 N4 photocatalytic layer, SnO2 electronic acceptor layer and muscovite sheet protective layer, with the aim to purify the surrounding environment. The construction of muscovite sheets into photocatalytic cement can keep the photogenerated carriers from the alkali ionic species in cement, reducing the recombination probability. What's more, the muscovite sheet layer can also prevent the products of the photocatalytic reaction from accelerating the carbonation of cement. Hence, the presence of muscovite sheets helps to solve the stubborn problems of traditional photocatalytic cement, improving the stability of photocatalytic cement. Moreover, due to the suitable bandgap position, the SnO2 /g-C3 N4 heterostructures have been devised to enhance electron-hole separation and interfacial charge transfer. By degrading Rhodamine B stains and volatile isopropyl alcohol, it has been found that the visible-light photocatalytic activity can be improved dramatically because of the functional modules. Consequently, this design provides promising outdoor use and will be of important significances to the development of green construction industry.